CONSUMER PREFERENCE ANALYSIS ON CHOOSING MINIMARKET WITH CONVENIENCE STORE CONCEPT IN BANDUNG (Study in Circle K, Indomaret and Alfamart in 2014) - Citra Dwi Setiawati Rustam; Damayanti Octavia (Conference In Business, Accounting, And Management (CBAM), 2015)
Today, minimarket competition in Bandung is very tight. It seen by minimarket in Bandung was overload by Dinas KUKM Perindag of Bandung. Until december 2013, Dinas KUKM Perindag of Bandung has registered 615 minimarket in Bandung, while tolerance number of minimarket in Bandung is only 360 units. This fact show that minimarket competition in Bandung is very tight and need a research about how the consumer preference of minimarket with convenience store concept in Bandung. It aims to understand consumer preference of minimarket with convenience store concept in Bandung. Attributes on this research based on retail mix elements that are merchandise assortment, price, communication mix, store design and display, customer service and location. Analysis technique used was conjoint analysis that produces the value of utilities and important of any attributes and level. Data collection is done by spreading the questionnaire to 400 respondents. The result of this research showed that consumer preference on choosing minimarket with convenience store concept are price atribute being the first preference with importance value 33,69%, location atribute with importance value 21,60%, store design and display atribute with importance value 16,26%, communication mix atribute with importance value 13,19%, merchandise assortment atribute with importance value 12,01%, and customer service atribute with importance value 3,22%. The result showed preferences of consumers in choosing minimarket with convenience store concept is convenience store which sets the low price, having adequate of parking area, comfortable store, do discount program, always available product on shelf/ refrigerators and the servants serving personally. Keywords : Consumer preference, Convenience store, Retail mix, and Conjoint analysis.